Family producers trajectory. Andrés Coliqueo Community. Freire Commune - Bravo Cuervo, Jorge (2014)
This document is part of the results of the study called The Path of Agricultural Producers in the Pelleco Community (1986-2006),which was in continuance to the 1980s study called The Mapuche Smallholding/Farmstead Historical Development of Agriculturein Pelleco which gathered data in 1986 under the authorization of Bravo and Sotomayor (1992). The new study was aimed at as certaining the development of Pelleco family producers during the years 1986-2006. Also, to compare a typology of Mapuche farms to the typology established in 1986. This was a longitudinal study that included quantitative and qualitative data including household surveys, interviews with community leaders, and farmers relevant to the study. Due to the trajectory path of family farmers; it was possible to distinguishthe developments. Also it was possible to identify a process of restructuring its production system which was generated within families as a response to social needs and conditions presented in the natural and social environment.